Prévention de la délinquance : le rôle médiateur des pairs - Vitaro, Frank; Tremblay, Richard (Criminologie, 1998)
The objective of this study was to test whether friends' characteristics mediated the link between early reduction of disruptive behavior and later reduction of delinquency (through a prevention program). The prevention program includes two components : social-cognitive-skills training for boys and parent-skills training at home. It was applied over a two-year period when the subjects were 8- and 9-year-old. Subjects were low SES boys rated as disruptive by their kindergarten teachers. They were randomly assigned to a prevention or a control condition. Their friends ' aggressiveness was rated by classmates over a three-year period following the end of the prevention program. Subjects reported on their delinquent behaviors when they were 13- and 14-year-old. Results indicate that friends' aggressiveness partially mediated the impact of the program on preventing delinquency. However, compared to the control boys, other mediating variables might also have played a role.